2021
DOI: 10.1177/03635465211042314
|View full text |Cite
|
Sign up to set email alerts
|

Complications Related to Latarjet Shoulder Stabilization: A Systematic Review

Abstract: Background: In cases of recurrent anterior shoulder instability with a glenoid defect, Latarjet procedures are widely used for stabilization. Although complications with this procedure have been reported, few studies have comprehensively analyzed issues related to the Latarjet procedure. Purpose: To identify the overall complication rate of the Latarjet procedure used for anterior shoulder instability and to compare the rate of complications between arthroscopic and open approaches. Study Design: Systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 63 publications
(58 reference statements)
1
26
0
Order By: Relevance
“…38 However, we detected slight external rotation limitations, with a mean of 8.1° in adduction and 7.5° in abduction postoperatively, consistent with external rotation restrictions reported in previous studies using bone augmentation procedures for ASI. 6,19,49,56 Remarkably, a >10° external rotation limitation only occurred in those patients with preoperative hyperlaxity. Most of them successfully returned to sports, and only 1 patient with restricted ROM in all directions failed to return sports.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…38 However, we detected slight external rotation limitations, with a mean of 8.1° in adduction and 7.5° in abduction postoperatively, consistent with external rotation restrictions reported in previous studies using bone augmentation procedures for ASI. 6,19,49,56 Remarkably, a >10° external rotation limitation only occurred in those patients with preoperative hyperlaxity. Most of them successfully returned to sports, and only 1 patient with restricted ROM in all directions failed to return sports.…”
Section: Discussionmentioning
confidence: 94%
“…27,34,71 In the current study, all patients reported no recurrent dislocations or subluxations after FBB-DAS, except 2 patients (3.1%) with positive apprehension test findings, which is slightly lower than the 6.2% postoperative instability rate after the Latarjet procedure. 17,19 Moreover, recurrent instability after the Latarjet procedure is a tricky issue in certain high-risk patient populations. Privitera et al 52 reported an 8% redislocation rate and a 14% instability rate in contact and collision athletes treated with the Latarjet procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 8 , 9 On the other hand, despite the fact that the Latarjet procedure can significantly reduce the rate of redislocation, growing evidence in the literature indicates that it has plenty of postoperative complications, such as bone graft osteolysis and nerve injury. 10 , 11 , 12 ICBG procedure has similar drawbacks, and it requires an additional surgical site, making donor site morbidity also a concern. The reported complication rate of ICBG procedure is approximately 25%-30%, with infection hematoma, meralgia paresthetica, and lilac wing fracture being the main reasons of failure.…”
Section: Introductionmentioning
confidence: 99%